The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-3083.2006.01878.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Markers for Neonatal Sepsis: Comparing C‐reactive Protein, Interleukin‐6 and Immunoglobulin M

Abstract: This clinical study was conducted to evaluate the diagnostic value of C‐reactive protein (CRP), interlekin‐6 (IL‐6) and immunoglobulin M (IgM) in the early diagnosis of neonatal sepsis. The diagnostic values of each marker separately or in combinations were evaluated. The optimal cut‐off values of each marker in the diagnosis of neonatal sepsis were defined. Between December 2004 and March 2005, a total of 78 neonates at different ages with different diagnoses in a neonatal intensive care unit in North Jordan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 23 publications
3
47
4
1
Order By: Relevance
“…In sepsis proven cases, 28(73.7%) were males. Similar findings as elicited in our study were cited by Mohammad f. Ibraheem [16] ,M Khassawne et al [17] stating male infants are more likely to develop sepsis than females. Gestational age: In present study, 92.1 % of the cases of sepsis proven and 82.3% of sepsis probable cases had full term as gestational age.…”
Section: Discussionsupporting
confidence: 81%
“…In sepsis proven cases, 28(73.7%) were males. Similar findings as elicited in our study were cited by Mohammad f. Ibraheem [16] ,M Khassawne et al [17] stating male infants are more likely to develop sepsis than females. Gestational age: In present study, 92.1 % of the cases of sepsis proven and 82.3% of sepsis probable cases had full term as gestational age.…”
Section: Discussionsupporting
confidence: 81%
“…Khassawneh M et al [20] reported that a CRP level >4 mg/L gave the best derived cutoff value with 95.7% sensitivity, 88.9% specificity, 78.6% PPV, and 98% NPV.…”
Section: Late-onset Neonatal Sepsis (Los) Is a Life-threatening Condimentioning
confidence: 99%
“…Several acute-phase reactants such as C-reactive protein (CRP) and interleukin-6 (IL-6) have proven helpful in the diagnosis of an ongoing infection. However, the rate at which each marker begins to show elevations and the time to normalization differs with each marker (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%